Ischemic Heart Disease in the Context of Different Comorbidities - Costache, Irina-Iuliana; Mihai, Bogdan-Mircea; Badescu, Minerva Codruta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Ischemic heart disease is a cardiovascular condition with very high prevalence worldwide and a major source of morbidity and mortality, especially in the geriatric population. The management of coronary artery disease is one that requires high-level expertise. The presence of comorbidities, usually multiple at advanced ages, makes the diagnosis and therapy very challenging. In this setting, the effort of a multidisciplinary team is urgently needed to achieve integrated management of these cases, being the only one capable of leading to the best results for the patient.The purpose of this reprint is to bring together the experience of specialists in treating ischemic heart disease in the presence of major related conditions that require particular modulations of diagnostic and therapeutic interventions. The chapters address difficult areas of interference between ischemic heart disease and frailty, cancer, liver diseases, inflammatory bowel disease and the new SARS-CoV-2 infection. Special consideration is granted to cardiac remodeling and progression to heart failure. Niche topics such as acute coronary syndromes triggered by carbon monoxide poisoning are present as well. The book also contains a particularly interesting chapter dedicated to the genetic substrate of ischemic heart disease, which once again emphasizes the need for a multidisciplinary team approach to this disease.We consider the reprint an excellent source of information for medical practitioners who have to solve complex cases of ischemic heart disease.